Media & crime - Jewkes, Yvonne, 1966- (Los Angeles : SAGE, 2015)
This text guides you through all the key issues, ranging from news reporting of crime, media constructions of children and women, moral panics and media and the police to 'reality' crime shows, surveillance and social control.
Theorizing media and crime -- The construction of crime news -- Media and moral panics -- Media constructions of children : 'evil monsters' and 'tragic victims' -- Media misogyny : monstrous women -- Police, offenders and victims in the media -- Crime films and prison films -- Crime and the surveillance culture -- The role of the Internet in crime and deviance -- (Re)conceptualizing the relationship between media and crime.
Includes bibliographical references (pages 309-324) and index.
Keywords: Crime in mass media; Mass media and crime; Mass media and criminal justice; Crime in mass media; Mass media and crime; Mass media and criminal justice